Organizational change and human resource management interventions: an investigation of the Nigerian banking industry - Osibanjo, Omotayo Adewale; Adeniji, Adenike Anthonia; Abiodun, Joachim Abolaji (Serbian Journal of Management, 2013)
The objective of this paper was to study the relationship between human resource management interventionist strategies and organizational change; and flexibility that can make employees more adaptive and receptive to changes. Out of one hundred and sixty copies of questionnaire administered, one hundred and twenty three (123) were collected and analyzed. Structural Equation Modelling (SEM), a hypothesized relationship was tested using Amos 18 that allows test of complex relationships between variables. Our model shows that relationship exists among human resource management interventionist strategies and was consistent with organizational change in the studied industry. However, the study can be extended to other industries, for example manufacturing industry as well as industry within the merger and acquisition of companies.
Keywords: Nigeria; Banking Industry; HR Interventions; Organizational change